(untitled) (The Pakistan Development Review, 1984)
In this paper we will be primarily concerned with the effect of inflation on different income groups. Putting it another way, we are looking for an answer to the question, "What have been the differences in the degree of inflation in various income groups in Pakistan?". Though it is not in the purview of this paper to go into the causes and cures of inflation, we feel that it is necessary to give a brief discussion about inflation in general. The classical economists believed that inflation was a purely monetary phenomenon. The theory developed was popularly termed the ’quantity theory of money’ and the basic relationship postulated was that the rate of inflation is equal to the rate of growth of money supply. Keynes [6J attacked the quantity theory of money. stating that the immediate source of inflation was the excess of desired expenditure over output and thus established the income-and-expenditure approach to the determination of the level of economic activity and prices. Later, however, Keynes (7] addressed himself to the effects of inflation and advanced a theory which has since become a basis for the ’inflationary gap’ models.